Pharmacotherapy of giant cell arteritis and polymyalgia rheumatica: Prospects for the use of monoclonal antibodies to interleukin 6 - Evgeny L. Nasonov; Azamat M. Satybaldyev; Elvira N. Otteva; Tatiana V. Beketova; Andrey A. Baranov (Научно-практическая ревматология, 2024)
Giant cell arteritis (GCA) and polymyalgia rheumatica (RPM) are immune-mediated rheumatic disease (IMRDs), which typically develop in people over 50 years of age. Currently, GCA and PMR are considered within a single complex autoimmune-autoinflammatory pathology, defined as “GCA-PMR spectrum disease”. This was reflected in the development of general recommendations for pharmacotherapy within the framework of the “treat-to-tar get” strategy, although specific approaches to the treatment of patients with GCA and RPM differ depending on the clinical and pathogenetic characteristics of each nosological form. Glucocorticoids (GCs) are central to the treatment of GCA and RPM. Attention is drawn to the paradoxical discrepancy between the high effectiveness of GCs in the short term and the increasing severity of pathology associated with persistent inflammatory activity and the accumulation of organ damage induced by GCs in the long term, which indicates the need to improve therapy, primarily in the direction of optimizing the use of GCs. New opportunities for pharmacotherapy of GCA and RPM (as well as other IMRDs) are associated with the use of biologic agents that block the activity of cytokines involved in the immunopathogenesis of diseases, and in recent years, JAK (Janus kinase) inhibitors. Among pharmacological “targets,” special attention is drawn to interleukin (IL) 6, a pleiotropic cytokine involved in the development of inflammation, immune response, immunometabolism, cancerogenesis, vascular wall remodeling, etc. Currently, several biologic agents have been developed that are specific to both IL-6 receptor and IL-6: humanized monoclonal antibodies (mAbs) to the IL-6 receptor (tocilizumab), and human mAbs to IL-6 receptor (sarilumab and levilimab (BIOCAD)), humanized mAbs to IL-6 olokizumab (R-PHARM), etc. The article summarizes data regarding the effectiveness and safety of tocilizumab in GCA and RPM, recommendations for the use of IL-6 inhibitors in these diseases and discusses the prospects for further research.